Disulfiram: a novel repurposed drug for cancer therapy - Lu, Chen; Li, Xinyan; Ren, Yongya; Zhang, Xiao (Cancer chemotherapy and pharmacology, 2021)
Cancer is a major health issue worldwide and the global burden of cancer is expected to reduce the costs of treatment as well as prolong the survival time. One of the promising approaches is drug repurposing, because it reduces costs and shortens the production cycle of research and development. Disulfiram (DSF), which was originally approved as an anti-alcoholism drug, has been proven safe and shows the potential to target tumours. Its anti-tumour effect has been reported in many preclinical studies and recently on seven types of cancer in humans: non-small cell lung cancer (NSCLC), liver cancer, breast cancer, prostate cancer, pancreatic cancer, glioblastoma (GBM) and melanoma and has a successful breakthrough in the treatment of NSCLC and GBM. The mechanisms, particularly the intracellular signalling pathways, still remain to be completely elucidated. As shown in our previous study, DSF inhibits NF-kB signalling, proteasome activity, and aldehyde dehydrogenase (ALDH) activity. It induces endoplasmic reticulum (ER) stress and autophagy and has been used as an adjuvant therapy with irradiation or chemotherapy drugs. On the other hand, DSF not only kills the normal cancer cells but also has the ability to target cancer stem cells, which provides a new approach to prevent tumour recurrence and metastasis. Furthermore, other researchers have reported the ability of DSF to bind to nuclear protein localization protein 4 (NPL4), induce its immobilization and dysfunction, ultimately leading to cell death. Here, we provide an overview of DSF repurposing as a treatment in preclinical studies and clinical trials, and review studies describing the mechanisms underlying its anti-neoplastic effects.